Pengaruh Tata Kelola Pemerintahan, Penerimaan Pajak dan Ekspor Terhadap Perekonomian di Asia Pasifik - Dwi Mahriun; Dewi Zaini Putri (Universitas Negeri Padang, 2020)
This Study aims to examine and to analysis how the effect of governance, tax revenue and export on economy in Asia Pasific, the variables that used are control of corruption (X1), political stability (X2), tax revenue (X3), expor (X4) and economy (Y). The data used is panel data during the period 2010-2017, and sourced by data documentation and review of literature obtained from relevant institutions and agencies. This study using the panel data regression approach with the object of several developed and developing countries.The study found that: (i) control of corruption, tax revenue and export have a significant effect on economy, (ii) political stability have a insignificant effect on the economy, (iii) and simultaneously all of the independent variables in this study have a significant effect on the economy.